Revolutionizing orthopedic healthcare: a systematic review unveiling recombinant antimicrobial peptides - Pennone, Vincenzo; Rosini, Elena; Mascheroni, Elena; Gianola, Silvia; Castellini, Greta; Bargeri, Silvia; Lovati, Arianna B. (Frontiers in Microbiology, 2024)
The increasing demand for orthopedic surgeries, including joint replacements, is driven by an aging population and improved diagnosis of joint conditions. Orthopedic surgeries carry a risk of infection, especially in patients with comorbidities. The rise of antibiotic resistance exacerbates this issue, necessitating alternatives like in vitro bioengineered antimicrobial peptides (AMPs), offering broadspectrum activity and multiple action mechanisms. This review aimed to assess the prevalence of antimicrobial potential and the yield after purification among recombinant AMP families. The antimicrobial potential was evaluated using the Minimum Inhibitory Concentration (MIC) values against the most common bacteria involved in clinical infections.This systematic review adhered to PRISMA guidelines, focusing on in vitro studies of recombinant AMPs. The search strategy was run on PubMed, Scopus and Embase up to 30 th March 2023.The Population, Exposure and Outcome model was used to extract the data from studies and ToxRTool for the risk of bias analysis. This review included studies providing peptide production yield data and MIC values against pathogenic bacteria. Non-English texts, reviews, conference abstracts, books, studies focusing solely on chemical synthesis, those reporting incomplete data sets, using non-standard MIC assessment methods, or presenting MIC values as ranges rather than precise concentrations, were excluded. From 370 publications, 34 studies on AMPs were analyzed. These covered 46 AMPs across 18 families, with Defensins and Hepcidins being most common. Yields varied from 0.5 to 2700 mg/L. AMPs were tested against 23 bacterial genera, with MIC values ranging from 0.125 to >1152 µg/mL. Arenicins showed the highest antimicrobial activity, particularly against common orthopedic infection pathogens. However, AMP production yields varied and some AMPs demonstrated limited effectiveness against certain bacterial strains. This systematic review emphasizes the critical role of bioengineered AMPs to cope infections and antibiotic resistance. It meticulously evaluates recombinant AMPs, focusing on their antimicrobial efficacy and production yields. The review highlights that, despite the variability in AMP yields and effectiveness, Arenicins and Defensins are promising candidates for future research and clinical applications in treating antibiotic-resistant orthopedic infections. This study contributes significantly to the understanding of AMPs in healthcare, underscoring their potential in addressing the growing challenge of antibiotic resistance.